PENDAMPINGAN PEMODELAN STRUKTUR BANGUNAN MENGGUNAKAN SAP2000 BAGI TENAGA TEKNIS KONSULTAN DI KOTA PONTIANAK - Ashraf Dhowian Parabi; Arif Parabi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2026)
Technical staff of planning consultants in Pontianak City face significant challenges in comprehensively mastering the SAP2000 structural analysis software, which directly affects the quality of technical planning products they produce. This Community Service activity aims to improve the competence of technical staff at CV. Bhipraya Cipta, Pontianak City, in performing structural building modeling and analysis using SAP2000 independently, systematically, and in accordance with applicable SNI standards. The activity was conducted in one full day divided into two sessions: the first session covered theoretical material including the basic concepts of the finite element method, modeling procedures, and SNI 2847-based loading; the second session consisted of hands-on training in three-dimensional building structural modeling with seismic load analysis using response spectrum in accordance with SNI 1726:2019. The implementation method employed a combined approach of community education, demonstration-based training, technology dissemination, and mediation. Evaluation results using normalized N-gain showed an overall mean competence improvement of 55.8% (moderate category), with the highest achievement in SNI 2847-based loading input (N-gain 63.6%) and the lowest in seismic response spectrum analysis under SNI 1726:2019 (N-gain 45.7%). All participants were able to understand the SAP2000 interface and apply SNI-based loading, while most participants were able to independently perform three-dimensional structural modeling and interpret structural analysis outputs. This activity delivered positive impacts on the quality of internal planning processes at CV. Bhipraya Cipta and strengthened synergy between higher education institutions and the construction services industry in West Kalimantan.